Erythrocytes and their value in pathogenesis of parodontium inflammatory diseases - Cheremisina, V. F.; Bereznyakova, A. I. (Journal of Education, Health and Sport, 2019)
The value of experimental animals (white rats) erythrocytes in pathogenesis of parodontium inflammatory disease was searched. The dynamics of Hb changes, erythrocytes number and hematocrit were surveyed. Periodontitis was moulded by special diet. When periodontitis developed oxidative stress and enhanced generation of reactive oxygen species were observed as well as changes in the number of erythrocytes, hemoglobin and erythrocyte indices. The latter were caused by membrane destructive processes in erythrocytes, decrease in their absolute number due to hemolysis, and changes in hematocrit due to blood redistribution.